μ-1,2-Bis(diethylphosphino)ethane-κ(2) P:P′-bis{[1,2-bis(diethylphosphino)ethane-κ(2) P,P′]trichloridonitrosyltungsten(II)} - Avramović, Nataša (International Union of Crystallography, 2008)
The title binuclear compound, [W(2)Cl(6)(NO)(2)(C(10)H(22)P(2))(3)], contains two W atoms which are bridged by a bis(diethylphosphino)ethane (depe) ligand. The seven-coordinated tungsten(II) centres display distorted pentagonal–bipyramidal geometries with trans nitrosyl and chloride ligands. The title molecule lies on a crystallographic inversion centre. The ethane group of the non-bridging depe ligand is positionally disordered, with site-occupancy factors of 0.63 and 0.37. In the crystal structure, the binuclear molecules are linked by weak intermolecular C—H⋯O and C—H⋯Cl interactions. In addition, weak intramolecular C—H⋯Cl interactions are also present.